Komunitas Aghumi Sebagai Wadah Seni Perfomatif Berbasis ‘Tarot’ Melalui Perspektif Interaksionisme Simbolik Herbert Blumer - Syachputra, Arjuna Adji Pangestu Arifin; Zuryani, Nazrina; Tamim, Imron Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes symbolic communication practices within Komunitas Aghumi, an experimental performance art community utilizing ‘Tarot’ Card’ as its primary creative medium. Employing a qualitative approach and Herbert Blumer’s symbolic interactionism theory, the research explores how ‘tarot’ symbols function not only as tools of expression but also as catalysts for self-reflection, collective meaning-making, and negotiation of identity and emotional well-being among members. Findings reveal that ‘tarot’ symbols are deconstructed from their conventional meaning as magical divination tools into transformative mediums for art, mental health therapy, and self-reflection, processed into non-verbal language that facilitates empathetic dialogue and collective narratives in performances. The quest for “benang merah” (conceptual thread) or consensus-building among members through mechanisms like card shuffling, thematic discussions, and interpretative negotiations constitutes the core artistic practice, demonstrating symbolic flexibility aligned with Blumer’s principle that meaning arises from social interaction rather than inherent object properties. The community further affirms art’s role as social transformation through inclusivity, notably collaborations with neurodivergent groups (e.g., autistic children) that dismantle stigma and foster self-confidence. Symbols, language, and cognition integrate to create an egalitarian, transformative, and therapeutic communication ecosystem serving as implicit critique against reductive views of performance art, positioning art as a medium of empowerment and resistance against conventional meanings. The implications of this research are expected to raise awareness of the community’s existence, deconstruction of the ‘tarot’ meanings, and the value of inclusivity for vulnerable groups, thus contributing sustainably to their empowerment and the preservation of arts and the culture.